QUALITY EDUCATION & TRIBES: NEW APPROACH TO ATTAIN SUSTAINABLE DEVELOPMENT GOALS - Subhasree Pal; Dr. Parimal Sarkar (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Education is that bristle which assemblages all sustainable development goals in a single garland. SDG4 infers quality education which ensures all phenomena of human life in a happy index. Sustainable development ensures equitable development of all without compromising the needs of future generations. The main target of SDG4 has to furnish quality education to all and to develop requisite skills to set up a nation that will promote an ambience in which every child has got the opportunity to develop as per their preference and contributes to making a just, patient and democrat society specially for all including vulnerable groups. It simply alludes that the sustainable plan of nation should be framed without neglecting different world views of different social groups, without curtailing down the indigenous knowledge of marginalised groups and without prioritising their aged pedagogy. Amartya Sen in his famous book, ‘Poverty and Famine’ points out that people from marginalised groups with low literacy rates fail to avail democratic freedom in their every step. We can’t attain sustainable development by leaving them behind. Tribes are the prime vulnerable groups of India where their concentration is the 2nd highest in the World. But their literacy rate and socio-economic scenario in comparison to other social groups in India, are the bottommost. For mainstreaming them, from the very dawn of freedom, they have been allowed to get inclusive education. Based on Millennium Development Goals, they also get the opportunity to avail free and compulsory education along with different governmental schemes and projects specifically designed for them to boost them in path of Sustainability. But their dilapidated conditions arise the question of rethinking the design of sustainability for them through SDG4 education. The present paper shows a roadmap for using SDG4 education to uplift their literacy rates, improve their socio-economic conditions by assimilating their indigenous pedagogy, world views for framing quality education to create an economic zone for their progress and prosperity.